STEM education: A global imperative for national advancement and sustainable development - Yimer, Sirak Tsegaye (American Journal of STEM Education, 2026)
STEM education is crucial for nations aiming to develop knowledge-based economies and enhance global competitiveness. To effectively leverage 21st-century technological advancements, safeguard national security, and address global challenges such as climate change and food insecurity, a significant improvement in the quality of STEM education policies and practices is essential. Successful implementation requires a thorough understanding of STEM’s core principles, philosophical foundations, practical applications, and relevant policy frameworks. This critique paper examines the status of key strengths and weakness of the diverse STEM education policies and practices implemented across developed nations. It intends to address the global knowledge and awareness deficit and improve understanding, about the importance of strategically investing in high-quality STEM education, particularly among developing countries.